Administração de maltodextrina em cavalos submetidos a teste de exercício progressivo e a exercícios sequenciais de alta intensidade e curta duração em esteira - Nitta, Thiago Yukio [UNESP] (2015)
The aim of this study was to evaluate the effect of acute administration of maltodextrin on the physiological and metabolic responses of horses submitted to standard incremental exercise test (TPEP) and sequential sessions high intensity exercise and rapid acceleration (Sequential Test Exercises - TES ) on a treadmill. Therefore, the study was divided into two steps: Study 1 was carried out to determine the effect of maltodextrin orally administered acutely in response to three amounts (0.2 g / kg, 0.4 g / kg; 0.6g / kg) on glucose and insulin curves of horses at rest, allowing determine the amount of maltodextrin to present greater persistence of blood glucose concentrations associated with lower insulinemic stimulus, and the second study that evaluated the effect of maltodextrin in response to two types exercises: TPEP and TES. Eight were used adult horses of the Arab horses, gelding were randomly divided into two groups of four animals that underwent two treatments, supplemented with maltodextrin (GM n = 8) and control (CG n = 8). Animals was used to GM received 0.4 g / kg of maltodextrin while undergoing GC received carboxymethylcellulose orally 30 minutes before exercise. The TPEP was performed on a treadmill with incline of 6% and consisted of sequential stages of progressive speeds of 1.8 m / s for a period of 5 minutes, followed at 4.0 m / s for 3 minutes, 6.0 m / s per 2min, and subsequent phases 7,0, 8.0; 9.0 and 10,0m / s for 1 min at each speed, or even when the horses could not keep galloping even being stimulated. The TES followed the protocol with an active heating period of speed of 1.7 m / s for 1min (0% incline), trot to 3.5 m / s for 5 minutes (0% incline) and step-by-1.5m / s for 5 minutes (6% incline), at the end of this period, the speed of the treadmill was quickly increased to speed corresponding to 105% of HRmax maintained for 50s. After this period, called sprint, the speed was immediately reduced to ...